Tinjauan Yuridis Permasalahan dan Tantangan Pengadaan Tanah dalam Kerangka Proyek Strategis Nasional (PSN) - Mustika Prabaningrum Kusumawati (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
This study aims to examine the legal review issues of juridical review of the problems and challenges of land acquisition within the framework of the National Strategic Project (PSN). This research is normative legal research with statutory and conceptual approaches. The results of the research show that the state itself has become the largest developer and ensures that its development targets are met, even by coercive means when necessary. In this case, spatial planning becomes an instrument for the state in achieving these development targets which in turn causes injustice for those whose living space is only designed to serve as a center for capital circulation. Therefore, the procurement must be announced in a transparent manner and the land to be acquired must be determined in advance before the work is carried out. This is expected to be a win-win solution for the government and affected communities so that the achievement of national strategic projects (PSN) can run well and smoothly and the affected communities are no longer the ones whose interests suffer the most.